1980
DOI: 10.1021/j100461a009
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and equilibria of cryptate formation in propylene carbonate

Abstract: Stability constants and dissociation rates of alkali metal cryptates have been measured in propylene carbonate, and the corresponding formation rates obtained from a combination of the two. Qualitatively, the variation in stability constants with cation size and ligand is similar to that in water, but the complexes are up to 107 times more stable in propylene carbonate. It is shown that for a given ligand the free energy transfer of the cryptates from water to propylene carbonate varies systematically with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…There are a number of effects common to most crystal structure determinations which may introduce systematic errors. In this analysis there is a shrinkage of the average bond lengths involving atoms which have a large (10) Momany, F. A.; Carruthers, L. M.; McGuire, R. F.; Scheraga, FI. A. J. Phys.…”
Section: Methodsmentioning
confidence: 99%
“…There are a number of effects common to most crystal structure determinations which may introduce systematic errors. In this analysis there is a shrinkage of the average bond lengths involving atoms which have a large (10) Momany, F. A.; Carruthers, L. M.; McGuire, R. F.; Scheraga, FI. A. J. Phys.…”
Section: Methodsmentioning
confidence: 99%
“…Results of kinetic and thermodynamic studies in propylene carbonate (PC) have already been reported. 3 A considerable amount of thermodynamic data on ion-solvent interactions in these solvents exists. 4 The results are analyzed according to the solvent dependence of the free energies of the various species M"+, L (=Cry), and ML""1" (=MCry"+) in eq 3.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) Protonation of(2,1,1)D + in CH30D.-The experimental techniques, ranges of concentration, and methods of analysis of the data are the same as those described above for measure- kDDA "1 ments in MeOH. The only difficulty was in deciding upon the value of the equilibrium constant, K, to be used in equation (12), as pK, values were not available in MeOD. Based on studies of weak acids in H 2 0 and D 2 0 l9l2O which show that for acids of similar strength ApK ( H 2 0 -D 2 0 ) is almost constant [e.g.…”
Section: Rate Constants Calculatedmentioning
confidence: 99%
“…Initial concentration of [(2,1,1)H]A. Equilibrium concentrations calculated using K = 2.0 x from equation(12) with kHA = 1.41 x lo3 mol-' dm3 s-I and K = 2.0 x…”
mentioning
confidence: 99%